A recommendation system for repairing violations detected by static architecture conformance checking. (25th September 2013) - Terra, Ricardo; Valente, Marco Tulio; Czarnecki, Krzysztof; Bigonha, Roberto S.
Summary This paper describes a recommendation system that provides refactoring guidelines for maintainers when tackling architectural erosion. The paper formalizes 32 refactoring recommendations to repair violations raised by static architecture conformance checking approaches; it describes a tool—called ArchFix—that triggers the proposed recommendations; and it evaluates the application of this tool in two industrial‐strength systems. For the first system—a 21 KLOC open‐source strategic management system—our approach has indicated correct refactoring recommendations for 31 out of 41 violations detected as the result of an architecture conformance process. For the second system—a 728 KLOC customer care system used by a major telecommunication company—our approach has triggered correct recommendations for 624 out of 787 violations, as asserted by the system's architect. Moreover, the architects have scored 82% of these recommendations as having moderate or major complexity. Copyright © 2013 John Wiley & Sons, Ltd.